PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SISWA - Siti Lestari; Astri Setyawati (Jurnal Ilmiah Matematika Realistik, 2026)
Students are encouraged to actively participate in problem-solving by utilizing past knowledge through the PBL paradigm. Teachers that often talk in front of the class discourage students from voicing their thoughts and impede the growth of critical thinking abilities, in addition to seldom involve students in the mastery of subject concepts. The purpose of this study is to investigate how using the PBL approach affects the learning results of SMA Kartikatama Metro eleventh-grade students. In order to gather data for this study, an experimental method with a quantitative approach was employed. The experimental class at SMA Kartikatama Metro was instructed utilizing the PBL paradigm employing a pretest–posttest control group design. According to the findings, the implementation percentage of learning activities utilizing the PBL model was 85% at the first meeting and rose to 90% during the second. The control group, on the other hand, scored 85% in the second meeting and 71% in the first. These results suggest that student learning outcomes are significantly impacted by the PBL approach. The posttest hypothesis testing using the t-test, which yielded a computed t value of 3.14 in contrast to the t-table value of 1.99, supports this finding. The alternative hypothesis (H₁) is accepted since the computed t-value is greater than the table t-value. According to these findings, students who are taught using the PBL model obtain better learning outcomes than those who are taught using traditional teaching techniques like talks and question-and-answer sessions.